Creativity or Intelligence? That is not the question - Cecilia Elisondo, Romina; Silvio Donolo, Danilo (Anales de Psicología / Annals of Psychology, 2010)
The study of the relationship between creativity and intelli-gence has occupied an important place in the research of creativity. De-spite being one of the most developed topics of the field, current research still wondering about the connections between these complex phenomena. The present study, conducted in Río Cuarto (Córdoba, Argentina), analyses the relationship between creativity, measured with test CREA (Corbalán, Donolo, Martínez, Alonso, Tejerina and Limiñana, 2003) and intelligence, measured by the Elementary Test TEI Intelligence (Yela, 1980) and an adaptation of the Progressive Matrices Test Raven. Study participants were 962 pupils and university level. In the first part, we present theoretical considerations and preliminary studies about relationships between creativity and intelligence. In the second part, we define the general characteristics of the research consider-ing purposes, population studies, instruments, procedures and results found. Finally, we present some general concluding remarks about the particular study and the relationship between creativity and intelligence in general.